Congenital and infantile melanoma: Review of the literature and report of an uncommon variant, pigment-synthesizing melanom - Tannous, Zeina S. (2002)
Congenital and infantile types of melanoma are uncommon conditions for which there are limited epidemiologic data. The number of reported cases is small with several ascribed etiologies. We review the literature and report the first documented case, to our knowledge, of pigment-synthesizing melanoma in an infant. Reported cases of congenital and infantile melanoma were identified and categorized on the basis of disease origin. Dermatopathologic specimens from an infant given a diagnosis of pigment-synthesizing melanoma are described. Disease arising from medium and large/giant congenital nevi was most common, whereas reports of de novo and transplacental disease were infrequent. Death of approximately 40% of patients was noted within 18 months of diagnosis. Male infants accounted for approximately 74% of cases. The most commonly affected anatomic sites were the head and neck. The prognosis for congenital and infantile melanoma is poor. The high incidence of head-and-neck involvement and male predominance for disease suggest dispositions for both anatomic disease localization and sex. (J Am Acad Dermatol 2002;47:77-90.)